Keamanan Data Pada Perangkat Internet Of Things Menggunakan Metode Public-Key Cryptography - Marsyel Sampe Asang; Irwan Sembiring (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2017)
Developments of IoT in every sector gives a new problem, it is information security. There are many issues about data theft and hacking in IoT system, this is because the weak of system security. IoT device is a part of system that needs special care for that issues. This research focuses on data security in IoT decive like microcontroller that only has a limited resources. Firstly is implement public-key cryptography using RSA algorithm in the device. Then, make an analysis process to see the effectiveness and efficiency of the method. Finally result of this paper shows that implementation of public-key cryptography in IoT device for data security still make the device effective and efficient to work only for small key.